2019
DOI: 10.7717/peerj.6556
|View full text |Cite
|
Sign up to set email alerts
|

Effects of handling and short-term captivity: a multi-behaviour approach using red sea urchins, Mesocentrotus franciscanus

Abstract: Understanding the effects of captivity-induced stress on wild-caught animals after their release back into the wild is critical for the long-term success of relocation and reintroduction programs. To date, most of the research on captivity stress has focused on vertebrates, with far less attention paid to invertebrates. Here, we examine the effect of short-term captivity (i.e., up to four days) on self-righting, aggregation, and predator-escape behaviours in wild-caught red sea urchins, Mesocentrotus francisca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 45 publications
(55 reference statements)
0
8
0
Order By: Relevance
“…There is considerable understanding of the factors that cause stress and their physiological impact on marine vertebrate species, but in comparison, little is understood about the mechanisms of stress in invertebrate species such as sea urchins (Bose et al, 2019). It is known that stress events such as handling and temperature changes induce a stress response in behaviour (Bose et al, 2019), and in the cell population dynamics of the coelomic fluid (Shannon & Mustafa, 2015) of specific sea urchin species. Shannon and Mustafa (2015) showed that changes in the cell structure found within the coelomic fluid of Strongylocentrotus purpuratus had an impact on sea urchin mortality and hypothesized this reflected a reduced immune capacity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is considerable understanding of the factors that cause stress and their physiological impact on marine vertebrate species, but in comparison, little is understood about the mechanisms of stress in invertebrate species such as sea urchins (Bose et al, 2019). It is known that stress events such as handling and temperature changes induce a stress response in behaviour (Bose et al, 2019), and in the cell population dynamics of the coelomic fluid (Shannon & Mustafa, 2015) of specific sea urchin species. Shannon and Mustafa (2015) showed that changes in the cell structure found within the coelomic fluid of Strongylocentrotus purpuratus had an impact on sea urchin mortality and hypothesized this reflected a reduced immune capacity.…”
Section: Discussionmentioning
confidence: 99%
“…Shannon and Mustafa (2015) showed that changes in the cell structure found within the coelomic fluid of Strongylocentrotus purpuratus had an impact on sea urchin mortality and hypothesized this reflected a reduced immune capacity. Bose et al (2019) showed that handling stress was sufficient to significantly change the behaviour of wild caught Mesocentrotus franciscanus . Neither study postulated on the physiological changes that may be occurring and the results of these studies as well as the current study highlight that in addition to the ability to enhance (increase) the size of the roe it would be very beneficial to be able to measure the stress in captive sea urchins and set benchmarks for levels that result in higher mortalities or lower quantities and/or quality of roe.…”
Section: Discussionmentioning
confidence: 99%
“…The growth rate for the autumn, for the winter, and total growth were calculated independently. Growth rates in the autumn were calculated using the third week as the initial mass, since animals in all treatments lost weight during the first two weeks of the experiment, likely due to stress from the lab environment and not treatment effect (Bose et al ., 2019). The final pyloric caeca mass was standardized by using the organ to body mass ratio and an ANOVA and Tukey's HSD test was run using JMP Pro 13.…”
Section: Methodsmentioning
confidence: 99%
“…At both locations, self-righting assays were conducted under constant abiotic conditions with individual animals contained in the same seawater tank; the animals were permitted to feed up until the experiment. Behavioural trials were conducted in the original holding tank to minimize effects of handling on righting behaviour; long-term holding of the animals minimized effects of short-term captivity on self-righting (Bose et al ., 2019). Individuals were identified visually by tracking distinctive morphological characteristics.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, holothurids have a more basic and streamlined body plan, perhaps limiting their ability to alter righting responses, as evidenced by the single method of self-righting we observed. In addition, we conducted experiments in the same tank that the animals were held in for >7 months prior to the experiment to avoid confounding effects of captivity and handling (Bose et al, 2019), while Gutowsky et al (2016) conducted experiments less than one day after animal collection. Indeed, acclimatization time is reported to affect behavioural repeatability (O'Neill et al, 2018).…”
mentioning
confidence: 99%